A comparative assessment of nutritional eye health literacy as a preventive tool among gainfully employed and homemaker women in urban India - Deepshikha; Ali, Ayub (International Journal of Research in Medical Sciences, 2025)
Background: Nutritional eye health literacy (NEHL) contributes significantly to the prevention of diet‑related ocular disorders, especially in urban populations where micronutrient deficiencies and digital exposure are increasingly reported. This study compared NEHL between employed and homemaker women in India and evaluated a machine‑learning model for predicting high NEHL. Methods: A cross‑sectional study was conducted among 300 Delhi‑NCR women aged 25–55 years. A validated 35‑item NEHL questionnaire was used. A logistic regression model with a 70/30 train–test split predicted high NEHL. Performance metrics included accuracy, sensitivity, specificity, precision, F1 score and AUC. Results: Employed women exhibited significantly higher NEHL scores (75.8±8.2) versus homemakers (66.9±9.5; p<0.001). The predictive model performed strongly (accuracy 82%, sensitivity 78%, specificity 85%, precision 81%, F1 score 79%, AUC 0.88). Conclusions: Employed women demonstrated better NEHL. The predictive model reliably identified individuals at risk of low NEHL. Targeted interventions are recommended for homemakers.